Technology and practice for efficient development of coalbed methane horizontal wells in high-rank coal of Qinshui Basin - WU Xi (Youqicang pingjia yu kaifa)
The Qinshui Basin is the main production base of high-rank coalbed methane in China. High-rank coal reservoirs in this region exhibit diverse conditions for coal formation and reservoir development, complex geological structures, low permeability, pronounced reservoir heterogeneity, and significant challenges in reservoir stimulation, which led to early issues such as a low effective resource utilization rate, low gas production per well, and low development profits. By analyzing the characteristics of high-rank coal reservoirs and the development patterns of coalbed methane, this study identifies three key constraints to the efficient development of high-rank coalbed methane: (1) poor precision in selecting areas for efficient development; (2) limited adaptability of development technologies; (3) a mismatch between stimulation processes and coal reservoirs. Investigations into microstructures, coal body structures, in-situ stresses, and fractures—combined with an evaluation of various geological factors’ impact on production—enabled a multidimensional division of development units to identify the geological features of each unit. Consequently, a “five-element” evaluation index system for production potential in efficient development areas was established, and an optimization method for selecting efficient development areas for high-rank coalbed methane was formulated. Analysis suggests that due to the low permeability and strong heterogeneity of high-rank coal, horizontal wells can connect more coal seam fractures, thereby expanding the drainage and pressure-relief areas and reducing the flow resistance of gas and water. This possesses advantages such as high per-well gas production and improved economic benefits. For different geological zones and development stages, in accordance with the principle of “maximizing controlled reserves, maximizing gas production rate, and optimizing economic benefits”, an optimized horizontal well layout technology for high-rank coalbed methane was developed. On this basis, with the objective of “initiating a fracture network, creating new fractures, and controlling reserves”, key technologies were devised—primarily including energy-focused directional perforation, stepwise hydraulic fracturing for incremental production enhancement, a combined application of fine-powder sand, and synchronous well-group interference. At the same time, the process technologies of bridge-plug-and-perforation using active water as the main body and well-group synchronous interference operations were refined, leading to the establishment of a linear fracture network system conducive to gas production, achieving efficient hydraulic fracturing. The application of these research outcomes in the Qinshui Basin has enabled the efficient development of high-rank coal, with daily gas production per horizontal well doubling, the ultimate recoverable reserve per well increasing by 50%, and the productivity attainment rate of newly-built blocks surpassing 90%. When extended to other high-rank coalbed methane blocks in China, these advantages provide technical support and a demonstrative model for strengthening the coalbed methane industry.